Confucian timely mean and Christian discernment : Confucian-Christian dialogue for spirituality of discernment and applied ethics /: Confucian-Christian dialogue for spirituality of discernment and applied ethics. (2023) - Kim, Sŭng-hye, 1943-
No abstract available